2014
DOI: 10.1007/s00440-014-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and estimation in the planted partition model

Abstract: The planted partition model (also known as the stochastic blockmodel) is a classical cluster-exhibiting random graph model that has been extensively studied in statistics, physics, and computer science. In its simplest form, the planted partition model is a model for random graphs on n nodes with two equal-sized clusters, with an between-class edge probability of q and a within-class edge probability of p. Although most of the literature on this model has focused on the case of increasing degrees (ie. pn, qn →… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
427
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(440 citation statements)
references
References 40 publications
10
427
1
Order By: Relevance
“…For networks generated using this model the existence and location of the detectability transition has been rigorously proven for the case of two communities of equal size [6][7][8]. The transition is a continuous one, with the fraction of correctly classified nodes playing the role of order parameter.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For networks generated using this model the existence and location of the detectability transition has been rigorously proven for the case of two communities of equal size [6][7][8]. The transition is a continuous one, with the fraction of correctly classified nodes playing the role of order parameter.…”
Section: Introductionmentioning
confidence: 97%
“…A string of recent discoveries, however, have revealed that there are fundamental limits to our ability to detect community structure [2][3][4][5][6][7][8]. Using techniques from statistical physics and probability theory, it has been shown that there can exist networks that possess underlying community structure and yet that structure is undetectable.…”
Section: Introductionmentioning
confidence: 99%
“…This is because we can always 'see' the partition 'locally' in space, but there is no way to consistently piece together the small partitions in different regions of space into one coherent partition of the graph if λ is small. This phenomenon is new and starkly different from what is observed in the classical Erdős-Rényi based symmetric Stochastic Block Models (SBM) with two communities where the moment one can identify the presence of a partition, one can also recover the partition better than a random guess ( [37]). Moreover, such phenomena where one can infer the existence of a partition but not identify it better than random are conjectured not to occur in the SBM even with many communities [14], [5].…”
Section: Introductionmentioning
confidence: 55%
“…Conditionally on the labels, pairs of nodes are connected by an edge independently of other pairs with two different probabilities depending on whether the end points are in the same or different communities. Structurally, the sparse SBM is known to be locally tree-like ( [37], [1]) while real social networks are observed to be transitive and sparse. Sparsity in social networks can be understood through 'Dunbar's number' [15], which concludes that an average human being can have only about 500 'relationships' (online and offline) at any point of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation